LEGAL NORMATIVE FUNCTION AS THE LEGAL PROTECTION - R Moh Zahri (Universitas Airlangga, 2023)
Legal arrangements regarding the protection of workers in Indonesia are regulated in Law Number 13 of 2003 concerning Manpower, updated by Law Number 11 of 2020 concerning Job Creation. However, it was found that there are still many employers who pay their employees' salaries below the minimum wage set by the Pamekasan Regency Government. This has violated their legal obligations under the labor law even though legally the salary amount is the result of an agreement between the employer and the worker. This research will be using a normative-empirical research method where it will be seen how the implementation of existing laws with facts in the field occurs. The findings are that due to lack of literacy and public understanding of the law and the prevalence of low wages in Pamekasan Regency, this practice has become commonplace. A lawsuit to the court can be one way to enforce their rights.